PERUBAHAN PENGETAHUAN IBU SEBELUM DAN SESUDAH MEMBACA MEDIA LEAFLET TENTANG STUNTING PADA IBU ANAK BALITA STUNTING: PERUBAHAN PENGETAHUAN IBU SEBELUM DAN SESUDAH MEMBACA MEDIA LEAFLET TENTANG STUNTING PADA IBU ANAK BALITA STUNTING - Yaumil Fauziah; Fitri Khairani; Annisa Namirah Nasution (Universitas Aufa Royhan, 2024)
ABSTRACT Stunting is a condition where a child experiences growth disorders, so that his height does not correspond to his age due to chronic nutritional problems, namely long-lasting malnutrition. Health promotion through the media is one of the efforts made to convey health information messages to mothers of toddlers. One of the most effective ways to convey information about nutrition to mothers of stunted toddlers is by distributing leaflets, which can increase mothers' awareness about nutrition and help them overcome the problem of malnutrition that continues in their stunted children. The aim of this study was to find out how the knowledge of mothers of toddlers suffering from stunting changed before and after receiving the leaflet intervention. Stunting is a condition where a child experiences growth disorders, so that the child's height does not correspond to his age, due to chronic nutritional problems, namely lack of nutritional intake for a long time. Health promotion through the media is one of the efforts made to display health information messages that want to be conveyed to mothers of toddlers, such as leaflets which are the easiest to help with the nutrition education process which is easier to understand in increasing the knowledge of mothers of stunting toddlers. Distributing leaflet media can increase health knowledge and nutritional awareness among mothers to overcome chronic malnutrition in children who are stunted. The aim of this research was to look at changes in the knowledge of mothers of stunting toddlers before and after the leaflet intervention. This research used a